Effects of vitamin d supplementation on type 2 diabetes mellitus patients - Al Aziz, Syaied Auliya; Novitasari, Diana (Institute of Computer Science (IOCS), 2024)
In Indonesia, around 10.9% of the population has diabetes according to the 2018 basic health research data. It is important for people with diabetes to receive proper treatment to prevent the condition from getting worse. Recently, there have been studies suggesting that taking vitamin D supplements can help improve diabetes. This research aims to explore whether vitamin D supplementation can indeed help control type 2 diabetes mellitus. The approach employed in this investigation entails conducting a comprehensive analysis of existing literature, where relevant articles published in the past 10 years were analyzed based on specific keywords. After finding the appropriate literature, the writing process began. Vitamin D is a substance that acts like a hormone and can increase insulin production in the body. Lot of evidence have shown that taking vitamin D supplements can lower fasting plasma glucose levels, improve insulin resistance, and reduce HbA1c levels when given in high doses over a short period of time. Vitamin D deficiency has also been linked to poor glycemic control in type 2 diabetes mellitus, leading to higher HbA1c levels. Based on the findings from the literature review, it can be concluded that vitamin D supplementation is effective in treating type 2 diabetes mellitus, with a minimum daily dose of 1000 IU. Overall, the evidence suggests that vitamin D supplementation can be a valuable addition to the management of type 2 diabetes mellitus, potentially improving outcomes and overall health in affected individuals. Further research is needed to fully understand the mechanisms behind these benefits and to determine the most effective dosages and treatment protocols.